2019
DOI: 10.1016/j.jmb.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

An N-Terminal Extension to UBA5 Adenylation Domain Boosts UFM1 Activation: Isoform-Specific Differences in Ubiquitin-like Protein Activation

Abstract: Modification of proteins by the ubiquitin-like protein, UFM1, requires activation of UFM1 by the E1-activating enzyme, UBA5. In humans UBA5 possesses two isoforms, each comprising an adenylation domain, but only one containing an N-terminal extension.Currently the role of the N-terminal extension in UFM1 activation is not clear. Here we provide structural and biochemical data on UBA5 N-terminal extension to understand its contribution to UFM1 activation. The crystal structures of the UBA5 long isoform bound to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 53 publications
4
25
0
Order By: Relevance
“…However, Souhda et al have shown that the presence of the N-terminal region dramatically increases the affinity of ATP for UBA5, enabling ATP binding at low concentrations, at which the shorter isoform does not bind ATP. In addition, the activation of UFM1 is significantly faster in the presence of the N-terminal domain, which also stimulates the transfer of UFM1 from E1 (UBA5) to E2 (UFC1) 13. Ufmylation is the first known role of UBA5, however, it can also activate SUMO2, another ubiquitin-like protein,12 and it is possible that it has other functions that remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…However, Souhda et al have shown that the presence of the N-terminal region dramatically increases the affinity of ATP for UBA5, enabling ATP binding at low concentrations, at which the shorter isoform does not bind ATP. In addition, the activation of UFM1 is significantly faster in the presence of the N-terminal domain, which also stimulates the transfer of UFM1 from E1 (UBA5) to E2 (UFC1) 13. Ufmylation is the first known role of UBA5, however, it can also activate SUMO2, another ubiquitin-like protein,12 and it is possible that it has other functions that remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…One starts at the beginning of the adenylation domain (amino acid 57), and the other has an extension of 56 amino acids in its N-terminus (long isoform) [ 3 , 28 ]. While both isoforms function in vitro, we recently found that the N-terminal extension of the long isoform significantly increases the affinity to ATP (nanomolar range instead of high micromolar) and stimulates the transfer of UFM1 to the E2 enzyme [ 29 ]. Accordingly, R55H mutation at the N-terminus reduces ATP binding, resulting in defects in UFM1 activation and transfer to the E2 [ 30 ].…”
Section: Ufm1 Conjugationmentioning
confidence: 99%
“…Despite an ever-increasing wealth of knowledge regarding the structure and function of E1 enzymes, little is known about potential mechanisms that might exist to regulate their activities. In this issue, Wiener and colleagues present biochemical, biophysical, and structural data revealing that the activity of the noncanonical E1, Uba5, is modulated by an alternative splicing event that results in isoforms that differ only by the presence or absence of a stretch of 56 amino acids at the N-terminus of the enzymes (so-called long and short isoforms) [23]. All previous structural studies on Uba5 utilized the short isoform and while the overall structures of the adenylation domain resembled those of previously characterized E1s, several surprising features of the Uba5 adenylation domain were observed (Fig.…”
mentioning
confidence: 99%
“…In this study, Wiener and colleagues determined that the long isoform of Uba5 has a significantly higher affinity for ATP and a faster rate of UFM1 activation compared to the short isoform [23]. The authors narrowed down the region of the N-terminus responsible for these differences to residues 37–56 and further demonstrated that this region mediates a significant ATP-dependent increase in the thermal stability of Uba5 compared to the short isoform.…”
mentioning
confidence: 99%
See 1 more Smart Citation